Anomalous Cerebellar Anatomy in Chinese Children with Dyslexia - Yang, Ying-Hui; Yang, Yang; Chen, Bao-Guo; Zhang, Yi-Wei; Bi, Hong-Yan (Frontiers in Psychology, 2016)
The cerebellar deficit hypothesis for developmental dyslexia (DD) claims that cerebellar dysfunction causes the failures in the acquisition of visuomotor skills and automatic reading and writing skills. In people with dyslexia in the alphabetic languages, the abnormal activation and structure of the right or bilateral cerebellar lobes have been identified. Using a typical implicit motor learning task, however, one neuroimaging study demonstrated the left cerebellar dysfunction in Chinese children with dyslexia. In the present study, using voxel-based morphometry, we found decreased gray matter volume in the left cerebellum in Chinese children with dyslexia relative to age-matched controls. The positive correlation between reading performance and regional gray matter volume suggests that the abnormal structure in the left cerebellum is responsible for reading disability in Chinese children with dyslexia.